(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
Modern world football places high demands on the level of preparedness of athletes, so the development of physical and technical qualities at an early age is the basis for the future professional growth of a footballer. The aim of the study is to compare the level of physical abilities and technical skills of Ukrainian and Azerbaijani footballers aged 12-13 in conditions of martial law and peacetime. Participants: 13 footballers who play football at the VOLNA Children’s and Youth Sports School in Kharkiv, Ukraine, and 15 footballers aged 12-13 who play football at the Neftchi Football Club in Baku, Azerbaijan. Research methods: theoretical analysis and generalisation of scientific sources, testing of physical abilities and technical elements, methods of mathematical statistics. Results: The study was conducted from September 2024 to May 2025. The results of physical and technical fitness tests at the beginning of the preparatory period and at the end of the competitive period for the football teams of Kharkiv and Baku were analysed, and practical recommendations were provided to both teams. The experiment showed that Ukrainian young footballers significantly improved their physical fitness scores in three tests, while Azerbaijani athletes improved in only two. It was found that young footballers from both teams demonstrate a high level of most technical elements; the effectiveness of maintaining the achieved level of physical fitness in teams throughout the playing season was also confirmed; reliable differences were found in the results of the tests ‘Dribbling the ball in a zigzag pattern’, ‘Kicking the ball with the non-dominant foot’, ‘Standing on one leg while holding the ball on the dominant leg’, Ukrainian footballers demonstrated higher results compared to Azerbaijani footballers (p<0.05; p<0.01). Conclusions: The effectiveness of sports training is determined not only by external conditions, but also by the flexibility of the methodology, the adaptability of the coach and the motivation of the athletes, which ensures stable progress and a high level of preparedness.